Building versatile mobile apps with Python and REST : RESTful web services with Django and React - Yudin, Art (Apress, 2020)
Develop versatile iOS apps using Python with RESTful web services. This book will show you how to blend Django, a high-level Python Web framework, with Django REST, the powerful, feature-filled extension, to build iOS mobile apps. Using easy-to-follow examples, you'll begin by building a simple app using the RESTful Web API and iOS. You'll then work with traditional Django to create models and connect your App to the database. You'll also see how to serialize your data and create the RESTful API. The second part of the book introduces Xcode, a programming environment to develop iOS apps. Using Swift, the programming language for iOS, you'll design the actual app. Once you have your back-end in Django and a front-end in Swift, you'll connect them using our RESTful API. This will allow you to log in, browse places of interest, and rate them and leave comments. Guided by step-by-step instructions, Building Versatile Mobile Apps with Python and REST will demonstrate how easy it is to use Python to develop iOS applications. You will: Build Create-Read-Update-Delete functionality using RESTful Web Services Incorporate marketing into the design of iOS apps to stand out in the App Store Deploy your app to a live server and add it to Apple app store .